Reprint of: Extracellular matrix as a biological scaffold material: Structure and function. (1st September 2015) - Badylak, Stephen F.; Freytes, Donald O.; Gilbert, Thomas W.
Abstract: Biological scaffold materials derived from the extracellular matrix (ECM) of intact mammalian tissues have been successfully used in a variety of tissue engineering/regenerative medicine applications both in preclinical studies and in clinical applications. Although it is recognized that the materials have constructive remodeling properties, the mechanisms by which functional tissue restoration is achieved are not well understood. There is evidence to support essential roles for both the structural and functional characteristics of the biological scaffold materials. This paper provides an overview of the composition and structure of selected ECM scaffold materials, the effects of manufacturing methods upon the structural properties and resulting mechanical behavior of the scaffold materials, and the in vivo degradation and remodeling of ECM scaffolds with an emphasis on tissue function.